Pengaruh Disiplin Kerja, Pelatihan Kerja, dan Motivasi Kerja Terhadap Karyawan PT. PLN (Persero) UP 3 Tanjung Karang - Mufidah Zahro; Iskandar Ali Alam (Journal Of Business, Finance, and Economics (JBFE), 2023)
PT PLN (Persero) UP 3 Tanjung Karang workers' work discipline, job training, and motivation following the COVID-19 epidemic will be examined in this research. This research explores the impact of three independent factors on employee performance: work motivation (X1), job training (X2), and work discipline (X3) (Y). A sample of 34 surveys was obtained using Solvin from 159 workers. The analytical method is multiple linear regression with t-test, f-test, validity, and reliability. Results research prove significant effect of work discipline of 0.025, job training of 2.042, and work motivation of 2.042 on the performance of employees of PT PLN (Persero) UP 3 Tanjung Karang.